Supporting data for the manuscript "Dams threaten salmonids by triggering temperature-dependent proliferative kidney disease" - Magnus Lauringson (20878516) (2025)
Description of data of the study entitled "Dams threaten salmonids by triggering temperature-dependent proliferative kidney disease" by Lauringson et al.: Fish data - all data included on sampled brown trout - ID (specimen identification nr.), river name, sampling site coordinates, Location (downstream/upstream), sampling date, total mass in grams (TM), total length in mm (TL), red blood cell estimates in mm, total blood volume estimate in mm, haematocrit (hc), haematocrit mean across three capillaries (Hc_mean) kidney thickness in mm, body thickness in mm, Kidney-to-body-thickness-ratio (K/B ratio), average cycle treshold value, parasite load in copies of Tb per μL, average water temperature between 29th of June to 22nd of August. The file also features a metadata sheet. IXO files_LightCycler480 folder - output data from .ixo files, including metadata. IXO files contain the following irrelevant samples that were excluded from the analysis (i.e. rivers without relevant upstream/downstream samples, samples with low DNA concentration, older trout): no. 146 - 163; 204 - 237; 303 - 327; 488 - 508. Plates 1 to 6 contain samples, including DNA extraction negatives (DNA neg) and qPCR negatives (NTC). Plate 7 contains synthetic dilution series of the synthetic T.bryosalmonae fragment. Temperature data - all temperature measurements (4 times per 24 hours) from 2022 (12 rivers) and 2023 (2 rivers) from both loggers per site if both loggers were intact, coordinates included. Data code folder - R script used for statistical analyses and input data in Excel spreadsheet and CSV.